Student Profile of a Brazilian Public Dental School - Tango, Rubens Nisie; Komori, Paula Carolina; Araújo, Luiz Fernando; Bardini, Vivian Silveira dos Santos; Kaminagakura, Estela (Brazilian Dental Science, 2021)
Objective: The aim of this study was to assess the profiles of dental students at the ICT/CSJC-UNESP School of Dentistry and their preferred studying style preferences. Materials and methods: Data on age, sex, place of residence, first-choice course, secondary education background and study method preference were collected from an online questionnaire given in the second year dental materials course (first class) of the day and evening courses of the years 2016 to 2019. All data were tabulated and submitted to one-way ANOVA and to t test, both with ? = 0.05. Results: Most of the students were women living in São José dos Campos city who had chosen Dentistry as their first-choice course. Many were originally from other cities and lived in shared accommodation with friends. The majority stated that private high school was their main educational background. Conclusions: Although ICT/CSJC-UNESP students were from millennial and post-millennial generations, they preferred studying alone and in silence rather than studying in groups.